A new look at net balances in the European Union's next multiannual budget - Zsolt M. Darvas (Bruegel, 2019)
Whenever the European Union's budget is discussed, much of the political focus is on net balances - whether countries pay in more than they receive - rather than on the broader overall positive effects of EU spending. Thelargest net contributor countries have sought to limit their contributions,leading to the build-up of an ad-hoc, complex, opaque and regressivesystem of revenue corrections.To inform debate on the 2021-2027 EU budget, I estimated the impact on net balances of the 2018 European Commission multiannual budget proposal, under three scenarios: elimination of rebates for all of the 2021-2027 new budget period, gradual elimination of rebates and non-elimination of rebates. These estimates were done on the basis of the EU's "operating budgetary balance" indicator, and on the basis of a new and broader indicator, the "net direct balance". The calculation also takes into account the estimated net contribution of the United Kingdom to the 2021-2027 EU budget based on the draft EU-UK withdrawal agreement.Under the baseline scenario of the Commission's proposal, those member states that currently benefit from rebates would face between 0.01 percent of GNI and 0.06 percent of GNI increases in their net contributions to the EU budget, measured by the EU's operating budgetary balance indicator. Meanwhile, central and eastern European member states that received several percent of their GNI as net payments from the EU in 2014-2020 would face significant reductions, though they would still receive net payments of about two percent of their GNI in 2021-2027.The methodology in this paper can be easily applied to estimate the net balance implications of any new MFF proposal.
Keywords: 330